Implementation of 48 V Series-Input Parallel-Output Zero-Voltage Switching Converter Using Secondary Resonant Technique - Watanyu Meesrisuk; Anuwat Jangwanitlert (International Review of Electrical Engineering (IREE), 2021)
This research paper aims to propose a series-input parallel-output zero-voltage switching converter (SIPO ZVS converter) by using the secondary resonant technique for achieving the Zero-Voltage-Switching (ZVS) condition for all the main switching devices in the proposed converter. Two half-bridge converters are applied for the proposed converter, connected in series at the input side and in parallel at the output side of the proposed converter (SIPO technique). By using the SIPO technique, the voltage stress on the main switching devices is decreased to be a half of the input voltage or Vdc/2. This leads to the reduction of rated voltage of main switching devices. The rated current of the rectifier diodes is also decreased because of the current sharing behavior. Moreover, the phase-shifted control method is analyzed in order to comprehend the impact on the ripple current at the output side. Finally, the prototype of the proposed converter has been designed, built, and tested in order to confirm the effectiveness of the proposed converter.
Keywords: Advanced DC-DC Converters; Multilevel Inverters and Converters; Induction Heating and Inverter Technology